MiR-193b regulates breast cancer cell migration and vasculogenic mimicry by targeting dimethylarginine dimethylaminohydrolase 1. Issue 1 (December 2017) - Hulin, Julie-Ann; Tommasi, Sara; Elliot, David; Hu, Dong; Lewis, Benjamin; Mangoni, Arduino
Abstract Dimethylarginine dimethylaminohydrolase 1 (DDAH1) is responsible for metabolism of an endogenous inhibitor of nitric oxide synthase (NOS), asymmetric dimethylarginine (ADMA), which plays a key role in modulating angiogenesis. In addition to angiogenesis, tumours can establish a vascular network by forming vessel-like structures from tumour cells; a process termed vasculogenic mimicry (VM). Here, we identified over-expression of DDAH1 in aggressive MDA-MB-231, MDA-MB-453 and BT549 breast cancer cell lines when compared to normal mammary epithelial cells. DDAH1 expression was inversely correlated with the microRNA miR-193b. In DDAH1+ MDA-MB-231 cells, ectopic expression of miR-193b reduced DDAH1 expression and the conversion of ADMA to citrulline. In DDAH1− MCF7 cells, inhibition of miR-193b elevated DDAH1 expression. Luciferase reporter assays demonstratedDDAH1 as a direct target of miR-193b. MDA-MB-231 cells organised into tube structures in anin vitro assay of VM, which was significantly inhibited by DDAH1 knockdown or miR-193b expression. Mechanistically, we found miR-193b regulates cell proliferation and migration of MDA-MB-231 cells, whilst DDAH1 knockdown inhibited cell migration. These studies represent the first evidence for DDAH1 expression, regulation and function in breast cancer cells, and highlights that targeting DDAH1 expression and/or enzymatic activity may be a valid option in the treatment of aggressive breast cancers.